Impact of BSA and casein on chemical modification of muga silk fiber. Issue 3 (3rd March 2016) - Choudhury, Manasee; Talukdar, Bijit; Dass, Narendra Nath; Baruah, Kanak Chandra; Devi, Dipali
Abstract : The study reports on the effects of bovine serum albumin and casein on grafting of muga ( Antheraea assamensis Helfer) silk fibers using initiator 2, 2' azobisisobutyronitrile. FTIR studies confirm the chemical binding of the proteins onto muga fibers through shifting of the major amide bonds, accredited to grafting. Scanning electron microscopy imaging reveals rugged morphology of the grafted fibers, due to the imprints of granular proteins. Tensile strength of the fibers increases with the augmentation in grafting percent. The grafted fibers showed no loss in weight after chemical resistance measurement indicating stable bond formation between the proteins and the fibers. Moreover, the water retention capacity and dynamic contact angle study of grafted fibers suggest better hydrophobicity. Thus, the use of such eco-friendly grafting agents for enhancing the strength and stability of silk fiber proves to be more beneficial than to other chemical grafting agents in producing efficient and environment-friendly silk for various applications in textile and other biomaterial fields.